Pengaruh Mendengar dan Membaca Al-Quran Terhadap Tingkat Kognitif pada Pasien Stroke Pertama - Erida Fadila; Mulyana Abdullah; Ahmad Zaldi; Gamal Abdul Nasir Zakaria; Norhazlin Muhammad (Universitas Malahayati Lampung, 2024)
ABSTRACT Therapy in the world of health there are pharmacological therapies and non-pharmacological therapies. Listening and reading the Quran is part of non-pharmacological therapy for healing various diseases because the Quran has high spiritual and religious value and provides a calming effect to stroke patients withimpaired cognitive function or noble functions that occur in the form of impaired orientation, attention, concentration, memory and language and intellectual function. The purpose of the study was to determine the effect of hearing and reading the Quran on cognitive levels in the first stroke patient at Arjawinangun Hospital in 2022. This study used quantitative, quasi-experimental research design (pre and posttes with group control). The sample size was 40 responses, divided into 20 control group respondents and 20 intervention groupres pondents. Probability sampling random sampling technique. The results of the study obtained differences in cognitive levels before and after treatment (pharmacological and non-pharmacological therapy / listening and reading the Quran) in the intervention group and there was no difference in cognitive levels in the control group that was only given pharmacological therapy. In this study there is also the influence of age, sex, and history of stroke characteristics on the cognitive improvement of stroke patients.from the results of the study it is expected that this non-pharmacological therapy can be one of the complementary therapies in the treatment of stroke patients who experience cognitive impairment Keywords: Holy Quran, Cognitive Level, Stroke ABSTRAK Terapi dalam dunia kesehatan ada terapi farmakologi dan terapi non farmakologi. Mendengarkan dan menbaca alquran menjadi bagian terapi non farmakologi untuk penyembuhan berbagai penyakit karena Al-Quran memiliki nilai spiritual dan religi yang tinggi serta memberikan efek ketenangan kepada penderita stroke dengan gangguan fungsi kognitif atau fungsi luhur yang terjadi berupa gangguan orientasi, perhatian, konsentrasi, daya ingat dan bahasa serta fungsi intelektual. Penelitian untuk mengetahui pengaruh mendengar dan membaca Alquran terhadap tingkat kognitif pada pasien stroke pertama di RSUD Arjawinangun pada tahun 2022. Penelitian ini menggunakan kuantitatif, dengan desain penelitian quasi experiment (pre dan posttes with group control). Jumlah sampel sebanyak 40 respon, dibagi menjadi 20 responden kelompok kontrol dan 20 responden kelompok intervensi. Teknik pengambilan sample random sampling jenis probability sampling. Penelitian didapat perbedaan tingkat kognitif sebelum dan sesudah diberikan perlakuan (terapi farmakologi dan non farmakologi/ mendengar dan membaca alquran) pada kelompok intervensi dan tidak ada perbedaan tingkat kognitif pada kelompok kontrol yang hanya diberikan terapi farmakologi. Pada penelitian ini terdapat juga pengaruh dari karakteristik usia, jenis kelamin, dan riwayat stroke terhadap peningkatan kognitif pasien stroke. Terapi non farmakologi dengan mendengarkan dan membaca alquran dapat menjadi salah satu terapi komplementer dalam penanganan pasien stroke yang mengalami gangguan kognitif Kata Kunci: Alquran, Tingkat Kognitif, Stroke